Advances in Translational Research and Clinical Care in Pancreatic Cancer: Where Are We Headed?. (4th February 2019) - Satyananda, Vikas; Gupta, Rohan; Hari, Danielle M.; Yeh, James; Chen, Kathryn T.
Abstract : While significant advances have been made in the treatment of many different solid tumors, pancreatic cancer remains a glaring exception. Overall 5-year survival rates for pancreatic cancer remain in the single digits. While newer chemotherapy regimens such as FOLFIRINOX and nab-paclitaxel/gemcitabine have demonstrated modest improvement in survival benefit for metastatic disease and have improved the resectability rates of previously borderline or locally advanced tumors, clinically significant improvements from immunotherapy and targeted therapy remain to be demonstrated. Regardless, a wealth of basic science research in pancreatic cancer has been directed at understanding its aggressive biology and its resistance to therapy. We present a brief summary of key areas of laboratory research and its translation to clinical care.